Pengaruh Kualitas Makanan, Kualitas Pelayanan dan Persepsi Harga Warung Makan Mbak Linda Terhadap Minat Pembelian Ulang - Ramadhan, Calvin Raihan; Hidayatullah, Muhammad Sultan; Ihsan, Arfian Maulana; Wibowo, Yosep Hendra; Rahadhini , Marjam Desma (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to evaluate the impact of food quality, service quality, and price perception on the repurchase intention of customers at Warung Makan Mbak Linda, specifically among students of Universitas Slamet Riyadi Surakarta. The research adopts a quantitative approach using a survey method through online questionnaires, involving 50 respondents. Data were analyzed using multiple linear regression with SPSS software. The results indicate that individually, only the food quality variable has a significant effect on repurchase intention, while service quality and price perception do not show a meaningful impact. Collectively, the three independent variables do not significantly influence the dependent variable. The coefficient of determination shows that only 4.7% of the variation in repurchase intention can be explained by these three variables. These findings suggest that food quality is a key factor in determining repurchase intention, while other factors such as atmosphere, promotion, or location may need to be explored further.